2012
DOI: 10.3126/hren.v10i2.6588
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral huge fimbrial cysts with torsion of right fallopian tube

Abstract: A case of bilateral fimbrial cyst with torsion of right side is presented, occurring in a 32 year old female. She presented in outpatient department with pain abdomen and feeling of mass in lower abdomen since six months. Initial assessment of ovarian cyst was made. Ultrasound showed cystic structures in left adnexa and complex cyst in right adnexa. Laprotomy was performed and bilateral fimbrial cysts in fallopian tubes were identified with torsion on right side which was subsequently confirmed on histopatholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…Therefore, to confirm the diagnosis exploratory laparotomy as a part of surgical intervention and diagnosis was performed along with histopathological investigations that confirmed the existence of fimbrial end cysts on both sides. As stated by a previous study, POCs may occur in patients who have bilateral tubal ligation [4] which was found to be congruous with the present case, as the obstetric history reported by the patient described tubal ligation which can be considered as a cause of POCs. Therefore, while determining the differential diagnosis of acute abdomen in women, POCs must be considered [4].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, to confirm the diagnosis exploratory laparotomy as a part of surgical intervention and diagnosis was performed along with histopathological investigations that confirmed the existence of fimbrial end cysts on both sides. As stated by a previous study, POCs may occur in patients who have bilateral tubal ligation [4] which was found to be congruous with the present case, as the obstetric history reported by the patient described tubal ligation which can be considered as a cause of POCs. Therefore, while determining the differential diagnosis of acute abdomen in women, POCs must be considered [4].…”
Section: Discussionsupporting
confidence: 91%
“…As stated by a previous study, POCs may occur in patients who have bilateral tubal ligation [4] which was found to be congruous with the present case, as the obstetric history reported by the patient described tubal ligation which can be considered as a cause of POCs. Therefore, while determining the differential diagnosis of acute abdomen in women, POCs must be considered [4].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…They are reported more often in adults. [12][13][14] The current case presented with bilateral paraovarian cysts, one of them fitting the definition of a giant cyst. An initial presenting symptom was excessive vaginal bleeding which could have been due to an immature hypothalamo-pituitary-ovarian axis since no uterine or endocrinological cause could be identified.…”
Section: Discussionmentioning
confidence: 99%
“…Majority have been reported in young women. 2 Most of patients are asymptomatic. Symptoms are because of pressure effects of huge cyst, rupture or torsion, lower abdominal pain, discomfort, abdominal distension and menstrual irregularities.…”
Section: Discussionmentioning
confidence: 99%